Cholesterol Overload: Contact Sites to the Rescue!. (December 2019) - Enrich, Carlos; Rentero, Carles; Grewal, Thomas; Futter, Clare E.; Eden, Emily R.
Delivery of low-density lipoprotein-derived cholesterol to the endoplasmic reticulum (ER) is essential for cholesterol homeostasis, yet the mechanism of this transport has largely remained elusive. Two recent reports shed some light on this process, uncovering a role for Niemann Pick type-C1 protein (NPC1) in the formation of membrane contact sites (MCS) between late endosomes (LE)/lysosomes (Lys) and the ER. Both studies identified a loss of MCS in cells lacking functional NPC1, where cholesterol accumulates in late endocytic organelles. Remarkably, and taking different approaches, both studies have made a striking observation that expansion of LE/Lys-ER MCS can rescue the cholesterol accumulation phenotype in NPC1 mutant or deficient cells. In both cases, the cholesterol was shown to be transported to the ER, demonstrating the importance of ER-LE/Lys contact sites in the direct transport of low-density lipoprotein-derived cholesterol to the ER.